Should We Consider Topical Silver Nitrate Irrigation as a Definitive Nonsurgical Treatment for Perianal Fistula? - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
BACKGROUND: Surgery is currently the sole treatment modality for anal fistulas. However, surgery is associated with complications such as permanent incontinence, which reduces quality of life. OBJECTIVE: To determine the rate of complete clinical healing of anal fistulas after irrigation of the fistula tract with silver nitrate solution as a nonsurgical treatment. DESIGN: Prospective single arm study. SETTING: Tertiary university hospital PATIENTS: Adult patients with symptomatic perianal fistula presenting between June 2012 and January 2013. INTERVENTION: Irrigation of the fistula tract with 1% silver nitrate solution. Irrigation was repeated every 2 weeks when necessary. MAIN OUTCOME MEASURES: The primary outcome measure was the rate of complete clinical healing. RESULTS: Fifty-six consecutive patients with anal fistula were analyzed. Of those, 29 (52%) had complete clinical healing without recurrence for a median of 10 months. The median number of irrigations needed for complete clinical healing was 4 (1-10). The level of satisfaction was excellent in patients with complete clinical healing. The frequency of complaints was the only independent factor that had an impact on healing; patients with intermittent discharge had a significantly higher rate of complete clinical healing 67%) than those with continuous discharge (40%). There were no notable complications. LIMITATIONS: Short follow-up, small sample size, and no comparisons. CONCLUSION: This study demonstrates that the application of silver nitrate solution often produces a favorable outcome in the treatment of anal fistula. This method may be considered as a first-line treatment for the disease because it is simple, performed on an outpatient basis, minimally invasive, and lacks the complications encountered with current conventional surgical modalities.
Keywords: Anal fistula; Silver nitrate; ANAL FISTULAS; SURGICAL-MANAGEMENT; IN-ANO; DISEASE